Determinants of Village Government Financial Performance: An Integrative Review from the Perspective of Agency Theory on Leadership, Governance and Internal Control: Faktor-Faktor Penentu Kinerja Keuangan Pemerintahan Desa: Tinjauan Integratif dari Perspektif Teori Agensi mengenai Kepemimpinan, Tata Kelola, dan Pengendalian Internal - Akhmad Mulyadi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Village financial management requires transparent, accountable, effective, and efficient governance because it involves public resources and financial accountability. Specific Background: Village government financial performance is associated with leadership, administrative capacity, public transparency, organizational culture, religiosity, inspection, delegation of authority, and internal control. Knowledge Gap: Previous empirical studies in Beji District report inconsistent findings regarding direct relationships among communication, leadership, education, and financial performance, indicating the need for an integrative synthesis. Aims: This study aims to synthesize three empirical studies on village financial performance, classify their determinants, compare significant and nonsignificant findings, interpret the results through Agency Theory, and develop an integrative conceptual model. Results: Using an Integrative Review, the study identifies three complementary mechanisms. Enabling mechanism comprises communication patterns and leadership style, with education level functioning as a moderator. Governance mechanism comprises public transparency, organizational culture, and official religiosity, all of which show significant relationships with financial performance. Control mechanism comprises inspection, delegation of authority, and internal control, which also show significant relationships. Communication patterns and education level do not show direct significant relationships, while education strengthens the communication–performance relationship and weakens the leadership–performance relationship. Novelty: The study integrates these determinants into enabling, governance, and control mechanisms within an Agency Theory framework. Implications: The model provides a conceptual basis for reducing information asymmetry, conflicts of interest, and opportunistic behavior in village financial management. Highlights: Leadership style shows a significant direct relationship with financial outcomes, while communication patterns do not. Education level operates as a moderator, strengthening one relationship and weakening another. Transparency, organizational culture, religiosity, inspection, delegation of authority, and internal control show significant relationships with the outcome. Keywords: Village Financial Performance, Agency Theory, Public Transparency, Internal Control, Integrative Review